2012
DOI: 10.3382/ps.2012-02357
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial resistance of Salmonella species isolated from chicken meats produced by different integrated broiler operations in Korea

Abstract: Prevalence and antimicrobial resistance profiles of Salmonella serotypes isolated from 7 chicken meat brands produced by different integrated broiler operations in Korea were determined. In total, 210 samples were collected from retail supermarkets in Seoul, South Korea, and analyzed for the presence of Salmonella. Of 210 chicken meat samples, overall Salmonella prevalence was 22.4%. Salmonella Enteritidis was the dominant serovar, with an isolation rate of 57.4% from the Salmonella-positive chickens, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
35
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 33 publications
19
35
3
Order By: Relevance
“…Previous studies have found that Salmonella Enteritidis is the most frequently reported Salmonella serovar detected in retail chicken meat and poultry slaughterhouses in South Korea (Chung et al, 2003;Woo, 2007;Kim et al, 2012), which is consistent with our findings.…”
Section: Resultssupporting
confidence: 95%
See 2 more Smart Citations
“…Previous studies have found that Salmonella Enteritidis is the most frequently reported Salmonella serovar detected in retail chicken meat and poultry slaughterhouses in South Korea (Chung et al, 2003;Woo, 2007;Kim et al, 2012), which is consistent with our findings.…”
Section: Resultssupporting
confidence: 95%
“…The ESBL-producing Salmonella might be transmitted to humans from animals via contact or consumption of contaminated food, thus complicating the treatment (Carattoli, 2008;Liebana et al, 2013;Clemente et al, 2013). Although the prevalence and antimicrobial resistance of Salmonella from poultry samples in South Korea have been reported in previous studies (Woo, 2007;Hyeon et al, 2011;Kim et al, 2012), limited data are available for their ESBL characteristics.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…If the lack of overlap in antibiotic resistance is an appropriate metric, then it is likely that goats are not a significant contributor to Salmonella contamination in these waters. In addition, the prevalence of multi-drug resistant Salmonella observed in this study is lower compared to prevalence reported from other food animals in Sudan (33.3 to 66.6%), Ethiopia (93.2%), United States (62%) and Korea (87.2%) (Fadlalla et al, 2012;Ferede et al, 2015;Khaitsa et al, 2007;Kim et al, 2012). This difference may suggest low antibiotics consumption in goat populations raised from Arusha area.…”
Section: Resultscontrasting
confidence: 52%
“…enterica serovar Typhimurium (Salmonella Typhimurium), a non-host-adapted Gram-negative intracellular pathogen, is capable of infecting a variety of animal hosts and humans (Barrow, 2007). In South Korea, the prevalence of Salmonella Typhimurium is widely reported in the broiler and layer chicken farms or poultry products (Rayamajhi et al, 2010;Kim et al, 2012;Choi et al, 2014). Chickens infected with Salmonella Typhimurium appear asymptomatic, but continue to shed the pathogen for long periods of time, with rare cases of systemic disease (Wales & Davies, 2011).…”
Section: Introductionmentioning
confidence: 99%